Na granicy Unii Europejskiej – pozycja europejskich terytoriów autonomicznych w dobie globalizacji i integracji. Przypadek Wysp Alandzkich - Jańczak, Jarosław (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2007)
The model of autonomy developed by the Aland Isles can provide a number of interesting solutions applicable in other territories. Territorial autonomy as a manner of ensuring the political and economic rights of the minority involves facing up to the challenges of European integration and globalization. It seems that the Aland Isles have successfully coped with this challenge. Firstly, they were able to present and promote their own interests during the accession negotiations in an efficient manner. Secondly, they maintained (and additionally strengthened by including it in the aquis communitaire) their separate, autonomous status and the guarantees of identity protection by virtue of limiting the rights of persons without domicile rights to purchase land and run business activity. Thirdly, they managed to obtain a special status excluding them from the process of indirect tax harmonization, thus ensuring considerable economic benefits. Fourthly, both Finland and the European Union confirmed their autonomy, demilitarization and neutrality allowing the Isles to retain their former status under the new circumstances. Fifthly, they obtained representation in the Committee of the Regions and a defined position on European matters in Finland. The skillful application of the existing solutions and the winning of an advantageous set of derogations and exceptions strengthened the position of the Isles both with respect to Finland and the international surroundings. The Isles’ economic, cultural and political protection was augmented. Alongside their participation in international organizations, such as The Nordic Board, the Aland Isles have remained active and discernible on the international arena.